MRI assessment of temporomandibular disorders: an approach to diagnostic and therapeutic setting. Issue 2 (April 2014) - Summa, S.; Ursini, R.; Manicone, P. F.; Molinari, F.; Deli, R.
Abstract : Aims: The aim of this study was to evaluate the relationship between the clinical and the radiological data obtained by magnetic resonance imaging (MRI) in patients with temporomandibular disorder (TMD). Methodology: The study group included 17 patients with symptoms of TMDs. The radiological assessments before and after therapy was evaluated by MRI; in the clinical analysis, signs and associated symptoms have been assessed. Results: With MRI before therapy, we were able to distinguish the specific type of TMD that each patient had. At the end of the treatment, a general improvement of the clinical status was noticed; MRI, however, showed the permanence of several degrees of condyle–disc incoordination in some patients. Conclusions: Certainly TMDs can be diagnosed without MRI; nevertheless, MRI gives us the possibility to obtain objective data of the patients concerned. Symptoms recorded during a clinical evaluation cannot be the only terms of diagnosis; MRI provides objective data in the diagnostic and post-therapy phases.